KAJIAN BENTUK FUNGSI MAKNA TRADISI METAMPELAN DI DESA LEMUKIH KECAMATAN SAWAN KABUPATEN BULELENG (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2024)
The implementation of Hindu piodalan in Bali varies from one region to another, this isbecause the traditions of each place are different, such as in Lemukih Village, Sawan District,Buleleng Regency, in every piodalan ceremony that is carried out there are traditions that arepart of it. namely the metampelan tradition. Based on this, the problem formulation is asfollows: 1. What is the form of implementation of the metampelan tradition in Lemukih Village,Sawan District, Buleleng Regency?, 2. What is the function of the metampelan tradition inLemukih Village, Sawan District, Buleleng Regency?, 3. What is the function of the metampelantradition in Lemukih Village, Sawan District, Buleleng Regency? The philosophical meaningof the metampelan tradition in Lemukih Village, Sawan District, Buleleng Regency? . Afterthat, the data was analyzed through: data collection, data reduction, data presentation, anddata conclusion. In the process of implementing the metampelan tradition, a process is puttogether so that the implementation goes well through the stages of the process of implementingthe metampelan tradition, namely: the preparation stage, the implementation stage, and thefinal stage in The implementation of the metampelan tradition in Lemukih village, this cannotbe separated from the time and place of implementation. The metampelan tradition hasfunctions such as: the function of rejecting evil, the function of purification, the function oftogetherness and the function of education. The philosophical meanings contained in themetampelan tradition are: the meaning of enriching religious kurtur in the metampelantradition, the meaning of ethics and the meaning of cultural preservation
Keywords: metampelan tradition, from and function of meaning